Electron microscopic imaging and NanoSIMS investigation on physiological responses of Aspergillus niger under Pb(II) and Cd(II) stress - Pan, Shang; Li, Zhaoyan; Wang, Jiayi; Li, Xuefei; Meng, Lingzi; Chen, Yunhui; Su, Mu; Li, Zhen (Frontiers in Bioengineering and Biotechnology, 2023)
In the bioremediation process, coexistence of lead (Pb) and cadmium (Cd) causes complex toxicity, resulting in the difficulty of bioremediation. This study investigated the physiological responses and bioaccumulation mechanisms of the typical filamentous fungus Aspergillus niger under the coexistence of Pb and Cd. Four treatments were set up, i.e., control, sole Pb, sole Cd, and coexistence of Pb and Cd. The morphology of A. niger were observed by scanning electron microscope (SEM) and transmission electron microscope (TEM), respectively. Then, nano-scale secondary ion mass spectrometry (NanoSIMS) was applied to accurately investigate the distribution of heavy metals in fungal cells under the coexistence of Pb and Cd. Finally, the metallogenic process and mineral types were simulated by Geochemist’s Workbench (GWB). The electron microscopic and NanoSIMS imaging showed that Pb and Cd were accumulated in both the extracellular and intracellular regions of the A. niger cells. In particular, the accumulated Pb content was ten times higher than Cd. However, Cd showed stronger toxicity than Pb to A. niger. Compared with the control treatment, Cd stress resulted in a two-fold increase of cell diameter and more extracellular substances, whereas the cell diameter increased nearly four times in the coexistence treatment. Moreover, the bioaccumulation of Pb was more intense than that of Cd during competitive sorption. The GWB simulation confirmed that Pb2+ can form multiple minerals (e.g., PbC2O4, PbHPO4, and Pb3(PO4)2, etc.), which significantly weakened its toxicity on the cell surface. This study elucidated the morphological characteristics of A. niger and competitive bioaccumulation under the coexistence of Pb and Cd, which would facilitate the application of microorganisms to the bioremediation of coexisted metals.